Purely Procedural Preferences - Beyond Procedural Equity and Reciprocity - Nadine Chlaß; Werner Güth; Topi Miettinen (Stockholm School of Economics, Stockholm Institute of Transition Economics (SITE), 2016)
Most research in economics models agents somehow motivated by outcomes. Here, we model agents motivated by procedures instead, where procedures are defined independently of an outcome. To that end, we design procedures which yield the same expected outcomes or carry the same information on other's intentions while they have different outcome-invariant properties. Agents are experimentally confirmed to exhibit preferences over these which link to psychological attributes of their moral judgment.
Keywords: C90; C78; D02; D63; 330; procedural preferences; experiment; institutional design